Estudo químico e farmacológico de Acnistus arborescens L. Schlecht e Physalis angulata L. - Veras, Maria Leopoldina (2006)
The present work describes the results of chemical and pharmacological studies of Physalis angulata and Acnistus arborescens (Solanaceae). The bioguided investigation of the ethanol extract from aerial parts of P. angulata resulted in the isolation and characterization of five withasteroids, which were identified as physalins B, D, E, F and 5a-ethoxi,6(3-hydroxy- 5,6-dihydrophysalin B. Of the ethanol extract from leaves of A. arborescens. The dichloromethane fraction from was responsible for the activity and its chemical investigation resulted in the isolation of nine compounds, including a new ceramide, and five withasteroids characterized as withaphysalin M, N, O, (17S,20R,22R)-5113,6,13:18,20-diepoxy-4/3,18- dihydroxy-1-oxovitan-2,24-dienolide and (17S,20R,22R)-5 [3,613: 18,20-diepoxy-4 p,18- dihydroxy-1 -oxovita-24-enolide. 3:18,20-diepoxy-4(3,18- hydroxy-1-oxovita-24-enolide. From the ethanol extract of the stems, a new ceramide together with the known compounds betulinic acid, docosanoic acid and a mixture of sitosterol and stimasterol, including their respective glucosides were isolated. The structures of all compounds were determined by IR, MS, and 111 and 13C NMR (1D and 2D) analyses. The in vitro cytotoxicity of physalins and withaphysalins was evaluated using a panel of nine tumor cell lines: CEM (lymphocyte leukemia), HL-60 (promyelicytic leukemia), HCT-8 (colon), MCF-7 (breast), B-16 (murine skin), PC-3 (prostate), MDA-MB-231 (breast), MDAMB-435 (breast) and K-562 (erytroleukemia). Except for physalin E and withaphysalin N, all compounds showed considerable citotoxicity. The physalins B and D showed in vivo antitumor activity, on sarcoma 180. In addition, the antimitotic effect of all physalins and withaphysalins was determined through sea urchin eggs assay (Lytechinus variegatus).